The Role of Artificial Intelligence in the Arabic Novel: Fadel Al-Azzawi's "The Fifth Fortress," a Comparative Analytical Study - Amin, Asst.L.. Sherine Star Hamad Amin; Salim, Asst.L. Raswl Kaka Law Salim (Sulaimani Journal for Humanities, 2025)
The research explores the impact of artificial intelligence on the Arabic novel, examining Fadel Al-Azzawi's novel The Fifth Fortress as a model for comparing human creativity with machine-generated production. With the increasing reliance on artificial intelligence in various fields, including literary writing, a fundamental question arises about the ability of machines to simulate human depth in literary expression. To what extent can artificial intelligence contribute to the production of an Arabic novel of literary value without compromising the essence of human creativity? The study focuses on the difference between the novel as a product of the writer's personal experience and texts generated by artificial intelligence based on pre-existing linguistic patterns. Al-Azzawi's novel conveys real suffering and honest personal experience, while the machine lacks self-awareness and emotion, rendering its literary production — despite the similarity of its structure — devoid of emotional honesty. The study warns against excessive reliance on artificial intelligence in writing, as it may lead to the loss of individuality and the repetition of styles. It also poses two central questions: Can artificial intelligence convey emotional reality with sincerity? And how does the reader assess the difference between a human text and a machine-generated one? The research seeks to emphasize that artificial intelligence can be a helpful tool in developing writing, but it cannot replace human experience in literature.
Keywords: Artificial intelligence; Arabic novel; Fadel AL Azzawi; The Fifth Fortress